In the Wake of the Crisis Leading Economists Reassess Economic Policy - Blanchard, Olivier; Romer, David; Spence, Michael; Stiglitz, Joseph E. (The MIT Press, 2012)
Prominent economists reconsider the fundamentals of economic policy for a post-crisis world. In 2011, the International Monetary Fund invited prominent economists and economic policymakers to consider the brave new world of the post-crisis global economy. The result is a book that captures the state of macroeconomic thinking at a transformational moment. The crisis and the weak recovery that has followed raise fundamental questions concerning macroeconomics and economic policy. These top economists discuss future directions for monetary policy, fiscal policy, financial regulation, capital-account management, growth strategies, the international monetary system, and the economic models that should underpin thinking about critical policy choices. Contributors Olivier Blanchard, Ricardo Caballero, Charles Collyns, Arminio Fraga, Már Guðmundsson, Sri Mulyani Indrawati, Otmar Issing, Olivier Jeanne, Rakesh Mohan, Maurice Obstfeld, José Antonio Ocampo, Guillermo Ortiz, Y. V. Reddy, Dani Rodrik, David Romer, Paul Romer, Andrew Sheng, Hyun Song Shin, Parthasarathi Shome, Robert Solow, Michael Spence, Joseph Stiglitz, Adair Turner